On the flexibility of group-equivariant convolutional neural networks - Roos, Lucas Johan (Stellenbosch : Stellenbosch University, 2025)
Roos, L. 2025. On the Flexibility of Group-Equivariant Convolutional Neural Networks. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/71005fe4-72f2-427b-a722-844be73ceb5c